Respuestas

¡La mejor respuesta!
2012-06-27T10:26:25+02:00

comensemos:

 

x^2 = 4cy 


despekamos "y" :


x^2 = 4cy


y = x^2

      4c


punto (p,q)


sacamos derivada para obtener la pendiente:


y' = (x^2)'

        4c

 

y' = 2x

      4c

 

y' =  x 

      2c

 

remplazamos x=p

 

y' =  p  -------> pendiente

      2c

 

recta tangente es:

 

m= p      punto:(p,q)

     2c

 

recta tangente:

 

(a,b) punto y m es pendiente

 

y-b=m(x-a)

 

por tanto:

 

y-q= p (x-p)

       2c 

 

2c(y-q)=p(x-p)

 

un gusto....=D